GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE STUDIES FOR YIELD AND FIBRE QUALITY TRAITS IN AMERICAN COTTON (Gossypium hirsutum L.) - B. MANSINGH NAIK (The Journal of Research ANGRAU, 2016)
Fifty genotypes of American cotton were evaluated during Kharif, 2015-2016 for genetic variability, heritability and genetic advance as per cent of mean based on 15 characters. High phenotypic coefficient of variation (PCV) and moderate genotypic coefficient of variation (GCV) values were observed for the traits, number of monopodia plant-1 and lint yield plant-1. High heritability coupled with high genetic advance as per cent of mean was recorded for characters viz., plant height (cm), boll weight (g) and micronaire (10-6 g in-1) indicating the preponderance of additive gene action making selection effective.